(U)WBG materials for RF piezoelectric acoustics - Jiashuai Xu; Zijun Ren; Kai Yang; Yujia Tu; Pengcheng Zheng; Shibin Zhang; Xin Ou; Xing Lu; Chengjie Zuo; Haiding Sun; Yansong Yang (APL Materials)
Ultra-wide bandgap/wide bandgap (UWBG/WBG) materials have revolutionized power electronics and ultraviolet solid-state lighting, attracting significant attention from researchers. However, beyond active devices, UWBG/WBG materials have also made remarkable contributions to radio frequency (RF) passive acoustic devices over the past decades. This paper provides a systematic and critical review of UWBG/WBG materials in RF passive acoustic applications, categorizing them into two functional groups: acoustic wave generators and acoustic wave restrainers. UWBG/WBG piezoelectric materials, including Al(Sc)N, LiNbO3 (or LN), GaN, and ε-Ga2O3, are explored as effective acoustic wave generators, while SiC and diamond are evaluated as acoustic wave restrainers due to their high phase velocity and thermal conductivity. This review examines the crystal structures, electrical, and acoustic (mechanical) properties of these materials, as well as their synthesis methods and chronological advancements in RF passive acoustic applications. By integrating recent research findings and technological trends, this review highlights the transformative potential of UWBG/WBG materials in developing next-generation RF communication technologies.